Desfechos em fetos e recém-nascidos expostos a infecções na gravidez - Kerolayne Aguiar Gomes da Silva; Keila Cristina Pereira do Nascimento Oliveira; Dara Moraes de Almeida; Edivânia dos Santos Sobrinha; Ewerton Amorim dos Santos; Géssyca Cavalcante de Melo; Raiany Samilli Pereira dos Santos
ABSTRACT Objective: To analyze outcomes in fetuses and newborns exposed to infections during pregnancy. Methods: Cross-sectional, quantitative study, carried out in a public maternity hospital in Maceió, Alagoas, Brazil. The sample consisted of 145 medical records of pregnant women admitted between 2015 and 2018 with possible vertically transmitted infections. Incomplete medical records or those that did not make it possible to describe fetal/neonatal exposure were excluded. The chi-squared test was used to verify the association between variables. Results: A greater occurrence of congenital syphilis was observed (28.8%). There was more than one outcome in the same individual, such as low birth weight (39%), respiratory distress (20.5%), oligohydramnios (20%), congenital malformation and small size for gestational age (10.8%). Maternal infections and the number of prenatal visits revealed an association with fetal/neonatal outcome (p ≤ 0.05). Conclusion: The data obtained indicate the occurrence of unfavorable fetal/neonatal outcomes when related to neonatal infections and indicate the need for strategies that strengthen the coping with vertical transmissions.